Value creating corporate social responsibility strategies of family and non-family firms: an interventionist perspective - García-Sánchez, Isabel-María (Journal of business ethics, 2025)
This paper presents a study on how corporate social responsibility (CSR) strategies create value amongst family and non-family firms. Additionally, in our study, we considered the moderating effect of independent directors on the relationship between CSR and firm value. Based on data drawn from companies operating in 61 countries over an 11-year period (i.e. from 2010 to 2020), our findings demonstrate that non-family firms derive market benefits from the governance improvements made by independent directors concerning CSR strategies. In contrast, the CSR strategies promoted within family firms are associated with lower firm value. However, this negative association is neutralised by the role played by independent directors, especially when the company is controlled by succeeding generations and not just by the founding one. These directors play a dissuasive role that leads family members to reassess their external socio-emotional preferences (reputation, image, etc.) in order to uphold the internal priorities of day-to-day decision-making. Our study has important implications for research and practice.